Possibility of realizing Green Innovation by Urban Social Enterprises in Indonesia - Suprobo, Filipus Priyo; Laksmana, Arsono; Wulani, Fenika (Advances in Social Sciences Research Journal, 2021)
This study examines environmental innovation as a prominent strategic issue in the current development of business practices. According to preliminary studies, profit-based business practices are used to determine the success of environmental innovation as superior competitiveness. Countries in Asia prioritize business development based on economic development, with social and environmental functions included in other agendas. However, this is contradictory with the phenomenon of Surabaya, where environmental-based urban social enterprises actors actually complement the role of the city government by carrying out the function of a hybrid organization (profit and social) with environmentally friendly practices. Therefore, this study aims to determine the possibility of urban social enterprises in Indonesia to obtain green innovation. This is a systematic research with 4 (four) strategic factors and conceptual models that makeup 6 (six) propositions formulated based on the scope of knowledge management theory and resource-based view. This conceptual model that connects green knowledge sharing, entrepreneurial orientation, dynamic capability, and innovation performance is still relatively rare and needs to be tested to determine its theoretical resilience. The novelty of this model is formulated from contextual urban and regional social enterprises in Indonesia, therefore, it is expected to provide ready-to-test opportunities to be duplicated in other urban areas in the world that have the same contextual organizational functions and environmentally friendly business base.